Educational expectations in the great recession: has the impact of family background become stronger? - Leire Salazar; Héctor Cebolla-Boado; Jonas Radl (Socio-Economic Review, 2020)
This article addresses the impact of economic climate, and particularly of the Great Recession, on the configuration of educational expectations among students around 140.167emyears old. We analyze expectations regarding educational attainment conditional on school performance and compare our results across countries with varying levels of economic growth over time. We expect a changing economic environment to impact on (a) the average level of educational expectations, (b) the association between social background and expectations, and (c) the association between school grades and expectations. Using pooled data from TIMSS for the years 2003, 2007 and 2011 among 8th graders for 24 developed countries, we estimate a set of country-fixed effects and hierarchical random-slope linear regression models. Most notably, our results indicate that economic down times depress educational expectations, especially among average-performing students, and lead to a growth in educational inequalities by family background.
Keywords: E02; I24; 330; economic growth; inequality; education; crises; uncertainty